Development of Budget Management System Using Visual Basic .NET and MySQL Database: A Desktop Application for Personal Financial Tracking - Janobe, Janobe (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study developed a desktop-based Budget Management System using Visual Basic .NET 2015 and a MySQL database to address the growing need for simple, secure, and offline financial management tools. The system enables users to record, update, and review income and expenses while automatically generating summaries of total income, total expenses, and current balance. Designed under the Software Development Life Cycle (SDLC) framework, it prioritizes usability, reliability, and privacy by storing all data locally and eliminating dependency on internet connectivity or subscription-based platforms. Testing results confirm that the system performs efficiently, remains stable even with large datasets, and is intuitive for users of varying technical backgrounds. Beyond its practical value, the system serves educational and developmental purposes by illustrating principles of database integration, user interface design, and software engineering in Visual Basic .NET. Although current limitations include manual installation and single-user operation, these provide clear directions for future improvement, such as automated setup, cross-platform compatibility, and advanced visualization features. Overall, the project demonstrates that accessible and privacy-oriented technology can significantly improve personal financial management while promoting financial literacy and independence.